Composition of fine particles in Carlsbad Caverns National Park and implications for sources and visibility impacts - Naimie, Lillian E., author; Collett, Jeffrey L., advisor; Benedict, Katherine B., committee member; Fischer, Emily V., committee member; Jathar, Shantanu, committee member (Colorado State University. Libraries, 2022)
The Carlsbad Caverns Air Quality Study (CarCavAQS) was designed to examine the influence of regional sources, including urban emissions, increased oil and gas development, wildfires and other biogenic sources, and soil dust on the park, including impacts on fine particle haze, ozone, and nitrogen deposition. Field measurements of aerosols, trace gases, and deposition were conducted from 25 July through 5 September 2019. Here the focus is on observations of the composition and concentration of fine particles and key trace gas precursors to understand important contributing species, their sources, and associated impacts on haze. Measurements focused on fine particulate matter (PM2.5) including mass, major ions, water soluble organic carbon (WSOC), and black carbon (BC) from various high time-resolution instruments as well as an Interagency Monitoring of Protected Visual Environments (IMPROVE) sampler. Supplemental measurements included denuder-filter pack sampling for inorganic gases (HNO3 and NH3) and a Picarro cavity ring down spectrometer for methane (CH4). High-time resolution (6-minute) PM2.5 mass ranged up to 31.8 μg m−3, with an average of 7.67 μg m−3. The main inorganic ion contributions were sulfate (avg 1.3 μg m−3), ammonium (avg 0.30 μg m−3), calcium (Ca2+) (avg 0.22 μg m−3), nitrate (avg 0.16 μg m−3), and sodium (avg 0.057 μg m−3). The WSOC average concentration was 1.2 μg C m−3. Inorganic ion concentrations had significant, sharp spikes in Ca2+, consistent with local dust generation and transport. Ion balance analysis suggests one period of acidic aerosol, the importance of ammonium and calcium in neutralizing sulfate, and significant reactions of nitric acid with sea salt and soil dust. The sums of PILS ion and WSOC concentrations, the latter multiplied by a factor of 1.8 to account for elements other than carbon, were not enough to reach mass closure with the TEOM PM2.5 mass concentrations, suggesting that insoluble species are also an important component of the aerosol at CAVE. IMPROVE sampler data, including insoluble species had good agreement between total PM2.5 mass and speciated PM2.5 aerosol mass. Sulfate is the major contributor to modeled light extinction in the 24-hour IMPROVE data set. Higher time resolution data had periods of significant light extinction from black carbon as well as sulfate, with a maximum 1-hour extinction value of 90 Mm−1. Analysis of transport patterns indicated clear enrichment of sulfate, BC, and CH4 during periods when transport came from the southeast, the direction of greatest abundance of oil and natural gas development. Air masses transported from the northeast, a region of high agricultural activity, were enriched in ammonia.
Keywords: haze; PM2.5; national parks; air quality